An assessment of the potential risks of Transfusion Transmitted Infections in patients transfused in Zimbabwean Hospitals - Rutsate, Ruvimbo; Mandisodza, Arthur; Chikwash, Vasco; Emmanuel, Jean; Mavunganidze, George; Nkomo, Sisodwa (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Blood safety remains the main objective for pretransfusion testing procedures. For the safetyof patients, blood is routinely tested for infectious agents in donated blood such as HIV, HBV,HCV and Syphilis. A retrospective study to determine the seroprevalence and trends of HIV,HBV, HCV and Syphilis in donated blood was carried out by reviewing records of theZimbabwean donors from January 2013 to December 2016. The prevalence of TTIs declined during this study period. HIV and HBV showed a significantdecrease due to improved donor selection criteria. There was no HCV detection from 2013.Other studies also showed declining HCV concentrations. Syphilis increased during the sameperiod. Despite the noted decline, the risk of TTIs remains high. There is need to reduce this risk intransfused patients by the introduction of the highly sensitive nucleic acid testing (NAT) test inZimbabwe to improve on the detection TTIs in donated blood.